The timeline of forest management in Malaysia towards achieving sustainable development goals / Noranida Mokthsim - Noranida, Mokthsim (2017)
Malaysia is committed to sustainable forest management (SFM) and this is reflected in the progress made on forest matters since UNCED. The National Forestry Policy was adopted in 1978 and revised in 1992, while the amendments of the National Forestry Act 1984 (amended in 1993) accorded greater emphasis on environmental protection and conservation of biological diversity. This dissertation presents a timeline approach in examining the relationships between forest resource development, forest degradation issues, and Malaysia’s efforts toward achieving sustainable development. The aim of the study was to examine from a timeline perspective how Malaysia’s growth trajectory, as determined by the utilisation of forest resources, had led to not only growth and expansion of its economic base as a common feature of development, but also the emergence of forest degradation issues. Four research objectives were established to answer the research questions in this study. The first objective was an examination into forest resources development in Malaysia, while the second objective was identification of forest management strategies undertaken by Malaysia. The third objective was to evaluate the effectiveness of the existing forest management strategies and the final objective was to identify the challenges in forest management related to forest resource development. To answer these objectives, data were collected from primary and secondary sources, where qualitative analysis was used to analyse the primary data and document analysis was adopted to analyse secondary data. The findings showed that the consumption of forest resource in Malaysia and the size of forest areas changes through time. In depth interviews with 10 respondents from different cohorts revealed the same opinion, which was that Malaysia cannot achieve sustainable development by 2020 if no alternative action is taken. The Strength, Weaknesses, Opportunity, and Constraint (SWOC) analysis was employed to determine various aspects relating to forest management in Malaysia. The last two decades also witnessed the increasing impact of trans-boundary problems in Malaysia that include both regional and global issues. These trans-boundary issues create another dimension that needs to be addressed in forest management, since at the national level, forest management faces tremendous challenges that need to be overcomed. Trans-boundary issues are difficult to manage because it affects many countries that have different priorities in their development of forest resources. Malaysia’s approach toward forest management is basically a three-pronged strategy that deals with management at the National, Regional, and Global levels.